Analysis of the Quality of Thoracic Radiography Results at Dr. M. Haulussy Ambon Regional General Hospital - Rusli, Rini Hatma; Ariyanto, Bambang; Malisngorar, Maritje Selfin J. (PT.Mantaya Idea Batara, 2026)
Introduction: Chest radiography is a fundamental imaging modality used to detect abnormalities of the lungs and heart. The quality of the produced images is critical to ensuring diagnostic accuracy. However, several challenges—such as variations in examination techniques, patient positioning, exposure parameters, and equipment condition—can compromise radiographic quality. This study aimed to analyze the factors influencing chest radiography quality and to evaluate the imaging standards applied at the Radiology Department of Dr. M. Haulussy Ambon Regional General Hospital.A mixed-methods approach, combining quantitative and qualitative analyses, was employed. Quantitative data were obtained from 100 chest radiograph samples, while qualitative insights were gathered through in-depth interviews with radiographers and radiologists. The quantitative analysis revealed that 65% of the radiographs were of good quality, 25% were adequate, and 10% required repetition. Qualitative findings indicated that limited routine training, aging equipment, and inconsistencies in radiographic techniques among practitioners were key factors contributing to reduced image quality.Based on these findings, practical recommendations were proposed to enhance operational standards and strengthen human resource competencies. The study provides a valuable basis for continuous quality improvement in radiology services, particularly in hospitals within Eastern Indonesia